Acid fast cysts in diarrheal stool samples of HIV positive patients - Mokkapati, Anuradha (International Journal of Research in Medical Sciences, 2017)
Background: Gastrointestinal infections are very common in patients with HIV infection or AIDS, and diarrhea is a common clinical presentation of these infections. Acid fast protozoans are very commonly responsible for diarrhea in HIV positive patients leading to death in many cases. Methods: The study group included 50 HIV seropositive patients suffering from diarrhea and the control group included 50 HIV seronegative patients suffering from diarrhea. The stool samples collected were concentrated using formol-ether concentration technique and stained using modified Ziehl-Neelsen’s staining procedure. Results: Among the diarrheal stool samples of HIV positive patients (n=50), 17 (34%) were positive for acid fast cysts, and among the HIV negative stool samples (n=50), 2 (4%) were positive for acid fast cysts. Cryptosporidium oocysts were detected in 15 (30%) and Isospora oocysts in 2 (4%) of the samples in the study group. Cryptosporidium oocysts were detected in 2 (4%) of the samples in the control group. There existed a significant difference between the positivity of HIV-positive and HIV-negative diarrheal stool samples. Conclusion: Timely and effective diagnosis could help in delivering appropriate treatment in an already immunocompromised patient.